2021
DOI: 10.1136/bjsports-2020-103514
|View full text |Cite
|
Sign up to set email alerts
|

Sports injuries and illnesses at the Lausanne 2020 Youth Olympic Winter Games: a prospective study of 1783 athletes from 79 countries

Abstract: ObjectiveTo describe the injury and illness characteristics among participating athletes during the Lausanne 2020 Youth Olympic Winter Games (YOG 2020), 9–22 January 2020.MethodsThe daily number of athlete injuries and illnesses were recorded (1) through the reporting of all National Olympic Committee (NOC) medical teams and (2) in the polyclinic and medical venues by the Lausanne 2020 medical staff.ResultsIn total, 1783 athletes from 79 NOCs were observed. NOC and Lausanne 2020 medical staff reported 228 inju… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
29
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(37 citation statements)
references
References 63 publications
7
29
0
1
Order By: Relevance
“…The knowledge finally found can be used for information management, query optimization, decision support, and data maintenance. For example, by analyzing the courses selected by students, we can understand which aspects of course learning students are more inclined to learn, so as to provide reference for course development [10]. Rule mining technology refers to extracting hidden, potential, previously unknown, and useful knowledge and rules from databases.…”
Section: Educational Data Miningmentioning
confidence: 99%
“…The knowledge finally found can be used for information management, query optimization, decision support, and data maintenance. For example, by analyzing the courses selected by students, we can understand which aspects of course learning students are more inclined to learn, so as to provide reference for course development [10]. Rule mining technology refers to extracting hidden, potential, previously unknown, and useful knowledge and rules from databases.…”
Section: Educational Data Miningmentioning
confidence: 99%
“…Moreover, unlike with alpine skiing ( Supej et al, 2013 ), aerodynamic drag apparently exerts little influence on the downhill performance of ski mountaineers. Even though ski mountaineers sometimes reduce control, even on challenging descents, to lessen muscle fatigue ( Gilgien et al, 2018b ; Supej et al, 2018 ; Supej and Holmberg, 2019 ), the incidence of injuries in connection with this sport is relatively low compared to other winter sports ( Palmer et al, 2021 ).…”
Section: Biomechanical Aspectsmentioning
confidence: 99%
“…[9][10][11][12][13][14] The proportions of XC skiing injuries appear similar between the OWG and WYOG (~5.4% vs ~5.1%, respectively) and between women and men (~5.9% vs ~5.0%, respectively). [9][10][11][12][13][14] Previous long-term studies (lasting ~1 year) have reported injury incidence rates in welltrained competitive and World Cup XC skiers of between 2.1 and 3.8 injuries per 1000 exposure hours, 5 15 16 and 11.4 injuries per 100 athletes per season, 17 respectively. Injuries to the lower extremities and lower back appear most common.…”
Section: Introductionmentioning
confidence: 84%